Storytelling, special needs and disabilities : practical approaches for children and adults - Grove, Nicola, 1948- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Now in a fully revised and updated second edition, this innovative and wide-ranging book shows how storytelling can open new worlds for individuals with special educational needs and disabilities. Providing a highly accessible combination of theory and practice, the contributors to this book define their own approaches to inclusive storytelling, describing the principles and theory that underpin their practice, whilst never losing sight of the joy at the heart of their work. Topics include therapeutic storytelling; language and communication; interactive and multi-sensory storytelling, and technology. Each chapter includes top tips, and signposts further training for practitioners who want to start using stories in their own work, making this book a crucial and comprehensive guide to storytelling practice with diverse learners. This new edition: Has been fully updated to reflect the way in which this field of storytelling has grown and developed, Uses a broad range of chapters, structured in a way that guides the reader through the conceptualisation of a storytelling approach towards its practical application. Includes an additional chapter, sharing the lived experiences of storytellers who identify as having a disability. Full of inspiring ideas to be used with people of all ages and with a range of needs, this book will be an invaluable tool for education professionals, as well as therapists, youth workers, counsellors and theatre practitioners working in special education"--
Forward -- Notes on contributors -- Introduction / Nicola Grove -- Therapeutic storytelling with children in need / Janet Dowling -- Feelings are funny things: using storytelling with children looked after and their carers / Steve Killick -- Healing stories with children at risk: the Story building approach / Sue Jennings -- What can teachers learn from the stories children tell? / Beth McCaffery -- Lis'n tell: live inclusive storytelling: therapeutic education motivating children and adults to listen and tell / Louise Coigley -- Interactive storytelling / Keith Park -- Speaking and listening through narrative / Bec Shanks -- Using narratives to enhance the language, communication and social participation of children and young people with speech, language, and communication needs / Victoria Joffe -- Creative use of digital storytelling / David Messer and Valerie Critten -- Storytelling in sign language for deaf children / Rachel Sutton-Spence -- Literature and legends: working with diverse abilities / Nicola Grove and Maureen Phillip -- Storytelling with all our senses: mehrSinn®Geschichten / Barbara Fornfeld -- Multi sensory stories in story packs / Chris Fuller -- Storytelling with nurturing touch: the story massage programme / Mary Atkinson -- Rich inclusion through sensory stories: stories from science / Joanna Grace -- Describing and evaluating the storytelling experience: a conceptual framework / Tuula Pulli -- Sensitive stories: tackling challenges for people with profound intellectual disabilities through multi sensory storytelling / Loretto Lambe, Jenny Miller and Maureen Phillip -- Social stories / Carol Gray -- Storysharing personal narratives for identity and community / Nicola Grove and Jane Harwood -- Personal storytelling with deaf blind individuals -- Gunnar Vege and Anne Nafstadt -- Personal storytelling for children who use augmentative and alternative communication / Annalu Waller and Rolf Black -- Self-created film & AAC technology for Daily Storytelling / Mascha Legel and Chris Norrie -- Learning to tell: teaching skills for community storytelling / Nicola Grove and Jem Dick -- The autistic storyteller: sharing the experience of otherness / Justine De Mierre -- Tales from the heart: testimony from storytellers with learning disabilities / Sayaka Kobayashi, the arts end of somewhere, and open storytellers -- Appendix: Storytelling organizations for resources and information.
"First edition published by Routledge 2012" -- Title page verso.
Keywords: Storytelling in education; Special education; EDUCATION / Special Education / General; EDUCATION / Teaching Methods & Materials / Arts & Humanities